ANTIBACTERIAL EVALUATION OF METHANOLIC RHIZOME EXTRACT FROM AN IN VIVO AND IN VITRO GROWN PTERIDOPHYTE, DRYNARIA QUERCIFOLIA (LINN.) J SMITH - Padhy, Ranjan; Kumar Dash, Santosh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Drynaria quercifolia (Linn.) J. Smith has been used in many herbal folklore medicines in Ganjam - Gajapati districts of Odisha state. Study pertains to its in vivo and in vitro antibacterial activities were undertaken to scientifically validate one of such therapeutic claim raised in the literatures, foreseeing the vulnerable state of the species. Methods: Methanolic extract from both the in vivo grown plant and in vitro grown callus were prepared and tested for their antibacterial efficacy against a wide range of bacterial pathogens concerned. Both agar well diffusion and disk diffusion methods were followed for evaluation of antibacterial activities. Development of callus was done using modified MS media supplemented with 20/gl sucrose and varied concentrations of auxins and cytokinins and the extract was prepared thereof. Antibacterial potency of both the extracts was measured in terms of zone of inhibition and statistical analysis was performed using Graph pad prism 6 software. Results: Methanolic extracts from both in vivo and in vitro samples had broad spectrum antibacterial activity on series of bacteria; however, bacterial species like Salmonella typhi, Shigella flexinneri, Streptococcus pneumoniae were resistant to both the samples. Further, the in vitro sample showed a higher degree of inhibition compared to the in vivo sample, was revealed. Conclusion: Study explored that the plant species is a potential source of antibacterial activity suggesting its in vitro culture for conservation and to obtain higher degree of antibacterial efficacy as well. Keywords: In vitro culture, Therapeutic claim, Folklore medicine, In situ/ex-situ conservation. INTRODUCTION